Pengaruh Waktu Fermentasi Madu dengan Bawang Putih Tunggal (Allium sativum L.) terhadap Daya Hambat Bakteri Propionibacterium acnes - Angela, Elva; Kunaedi, Aan; Ine Suharyani; Andriana, Andriana (MES Bogor, 2022)
Honey is a substrate that has widely used by the people of Indonesia for treatment, one of which is used to treat acne. Honey has antimicrobial inhibitory power, antimicrobial ability is also found in other natural ingredients, one of it is Single Garlic (Allium sativum L.). Community trend towards the two natural ingredients, one of which is by combining Honey and Single Garlic (Allium sativum L.) using the method of soaking Single Garlic (Allium sativum L.) in Honey. The purpose of the study is to determine the inhibitory power of honey bacteria from soaking / fermentation against propionibacterium acnes bacteria.Testing use the disc paper diffusion method with a sample of fermented Honey and a single Garlic (Allium sativum L.) against the length of honey fermentation time, positive control (Clindamycin 300 mg), and negative control (aquadest). Sample Honey and Garlic Sample (Allium sativum L.) were fermented length time at weeks 1,2,3 and 4. The results showed that the length of time honey fermentation can increase the inhibitory power of the growth of Propionibacterium acnes bacteria by the presence of clear zones around the disc paper. The diameters of honey fermentation in weeks 1,2,3 and 4 are 0.416 mm, 0.65 mm, 0.775 mm and 1.8 mm. The conclusion that the length of fermentation time of Honey and Single Garlic (Allium sativum L.) will increase in diameter in the clear zone of its inhibitory power known in the fourth week to have a maximum inhibitory power of 1.8 mm. Keywords: Fermented honey, Single Garlic,Inhibitory power of bacteria Propionibacterium acnes